Comparing the morphology and physiology of trees planted in containers and in-ground sites. Issue 4 (2nd October 2017) - Ow, Lai Fern; Ghosh, Subhadip
Abstract: Restricted root volume poses a constraint to the successful establishment of containerised trees. The potential for growth and survival in containers for urban forests is important to ensure a sustainable population of sizeable urban trees given the staggering pace of development. In this study, it was found that the restricted soil environment inside the containers had no effect on the morphometric and physiological characteristics of container trees. A positive relationship was found between xylem pressure potential and F v / F m . A stronger correlation between xylem pressure potential and soil water status was observed. This indicated the importance of soil water status for optimal photosynthetic function and overall tree growth. Biomass data indicated that container trees tended to allocate more carbon to leaves, stems and branches while in-ground trees channelled carbon into leaves and roots. The potential for growing trees in containers is a desirable alternative to in-ground planting, providing urban municipalities with the option to save and relocate trees when confronted with development. In doing so, cities can work towards the development of a sustainable population of medium to large urban trees.